Re-strengthening coordination and engagement platform for evidence-based policy research in Lao PDR - NPS Laos communication team (CGIAR System Organization, 2023)
Lao national policy researchers, international research partners, and in-country stakeholders from different agricultural development sectors discussed ways forward to implement evidence-based policy research during a consultation workshop on 11 October 2023 in Vientiane Capital, Lao PDR.